IMPLEMENTASI RASPBERRY PI SEBAGAI PENERIMA GELOMBANG FM PADA FREKUENSI VHF (136 MHz-174 MHz) MENGGUNAAN RTL-SDR 2832U - May Lia Khoironisa; Sigit Kusmaryanto; Ali Mustofa (Jurnal Mahasiswa TEUB, 2022)
Raspberry Pi (Raspi) is a single-board computer (single-board circuit; SBC) that can be used to run office programs, computer games, and as a media player to high-resolution video. The Raspberry Pi has advantages that resemble computers in general, in every way on the computer functions can also be done with the Raspberry Pi. This paper discusses the application of the Raspberry Pi 3b+ as a VHF receiver at a frequency of 136 MHz-174 MHz using RTL-SDR R2832U. The author uses Handy-Talkie as a transmitter for FM waves at a VHF frequency (136 MHz-174 MHz). Raspberry Pi 3 implementation with RTL-SDR R2832U to receive FM waves using GNU Radio and GQRX software. The operating system used in this research is Raspberry Pi OS. The results show that the Raspberry Pi device can be used to receive FM waves at the VHF frequency (136 MHz-174 MHz) with SNR 58.82 dB at 136.025 MHz Dipole antenna examined using VNA (Vector Network Analyzer) with length 52.4 cm on each side and linear shape that can receive signal with VSWR 1.48:1 on frequency 136-174 MHz and return loss -14.2 dBm on frequency 136 MHz. Keywords: Raspberry Pi, RTL-SDR 2832U, FM Receiver